Municipal Labor Demand in the Presence of Uncertainty: An Econometric Approach - Holtz-Eakin, Douglas; Rosen, Harvey S. (Journal of Labor Economics, 1991)
We specify a model of municipal labor demand when resource flows available to the municipality are uncertain. The model allows us to test the hypothesis that employment decisions are rational in the sense that they incorporate all available information at the time that the decisions are made. We find that, for our sample of communities, on the whole one cannot reject the hypothesis that labor demand is consistent with intertemporal utility maximization under uncertainty. However, small and large communities exhibit different behavior. The employment decisions of small communities are consistent with the model, while those of large communities are not.